Penerapan Ergonomi dalam Pembuatan Kursi Kerja Guna Meningkatkan Produktifitas Kerja Karyawan - Kholik, HM.; Estrimaz, Ayudina Puji (Jurnal Teknik Industri, 2002)
Evalry Konfeksi is a developing home industry in Tulungagung with woman's attire as it main product.Stitching section p lays important role here since most of work activities are centeredat this section. One facility that has a great impact is working chair, because with more ergonomic working chair the employees will be able to reduce boredom and fatigue at particular part of their body.This will eventually be able to minimize working time so that there will be an improvementon work output and productivity.From analysis on the research results upon 20 employees during 7 days of on-site observation, we get unimprovement on average work efliciency for each work element by22.05 %. The average working time of each element using the new designed working chair is in fact shorter if compared to those of using the old designed.This reduction is 5.72 minutes/product unit on average, thus there is an improvement on employees productivity.It can be concluded that using the new designed working chair will be capable in resulting in positive impact on company's output lmprovement.